Light pollution. Approach to the problem in Sants quarter (Barcelona, Spain) - Moreno García, Mª Carmen; Martín Moreno, Adán (Observatorio Medioambiental, 2016)
Light pollution is excessive or defective artificial night lighting, mainly in cities. Its negative effects are: diffusion to the sky, which hampers astronomical observation; light intrusion or penetration of light through the windows, preventing sleep; glare; and energy overconsumption. Once presented the concepts of light pollution and analyzed the types of luminaires, the case of Sants quarter (Barcelona) was studied. Transects through 21 streets and squares were conducted, and an extensive photographic inventory was made. Problems with light intrusion were detected in 57.1% of the pathways analyzed.
Keywords: Light pollution; Light intrusion; Street lighting; Luminaire; Sants quarter; Barcelona; Led; Sodium vapour.